Three-year functional, physical, and mental health outcomes after critical COVID-19: A prospective multicentre cohort study - Ingrid Didriksson; Dorit Töniste; Malin Hultgren; Martin Spångfors; Sara Göbel Andertun; Maria Nelderup; Anton Reepalu; Attila Frigyesi; Hans Friberg; Gisela Lilja (PLoS ONE, 2026)
Background The understanding of recovery after critical COVID-19 beyond the first year is limited. Objectives To describe changes in functional, physical, and mental health outcomes between 1 and 3 years among survivors of critical COVID-19 and to identify factors associated with incomplete recovery at 3 years. Methods A prospective multicentre cohort study of survivors of critical COVID-19 with follow-up at 1 and 3 years. The primary outcome was functional outcome, assessed using the Glasgow Outcome Scale-Extended (GOSE), which ranges from 1 to 8, with scores of 6 or less indicating incomplete recovery. Secondary outcomes included return-to-work, physical and mental Health-Related Quality of Life (HRQoL), life satisfaction, fatigue, psychological symptoms (anxiety, depression, post-traumatic stress disorder), and respiratory symptoms. Multivariable logistic regression was used to identify factors associated with incomplete recovery (GOSE ≤ 6) at 3 years. Results Among 191 of 210 eligible participants, functional outcome declined from 1 to 3 years, and participants with incomplete recovery increased from 32% to 45%. Worse outcomes were observed in mental HRQoL, fatigue, depression, and post-traumatic stress, while return-to-work rates, physical HRQoL, life satisfaction, anxiety, and respiratory symptoms remained stable. Younger age [OR 0.70 (95% CI 0.54–0.91), p = 0.008] and higher Clinical Frailty Scale score [OR 1.54 (95% CI 1.04–2.28), p = 0.029] were independently associated with incomplete recovery at 3 years. Conclusions Survivors of critical COVID-19 experienced a decline in functional outcome and worsening mental health between 1 and 3 years after ICU admission. Younger and frail survivors may require increased attention and support. Trial registration ClinicalTrials.gov Identifier: NCT04974775, registered April 28, 2020.